Bridging the Knowledge Gap: The Role of Research4Life in Advancing Academia in Nepal - Yadav, Chandra Bhushan (TULSSAA Journal, 2025)
Access to scholarly literature is a fundamental necessity for academic and research excellence. However, many developing countries, including Nepal, face challenges in accessing high-quality scientific resources due to financial constraints. The Research4Life programme addresses this issue by providing free or low-cost access to academic and professional databases through five specialized programs: HINARI, AGORA, OARE, ARDI, and GOALI. Nepal has significantly benefited from this initiative, with 553 registered institutions utilizing these resources to enhance research quality, support higher education, and promote innovation.